A method for preparing an oriented carbon nanotube-graphene / copper composite material

Through the synergistic effect of carbon nanotubes and graphene and external magnetic field regulation, directional carbon nanotube-graphene/copper composite materials were prepared, solving the problem of enhanced combination disorder in existing copper-based composite materials, significantly improving the material mechanical properties and conductivity.

CN115896518BActive Publication Date: 2025-02-11FUZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202211568540.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-08
Publication Date
2025-02-11
Estimated Expiration
2042-12-08

Smart Images

  • Figure CN115896518B_ABST
    Figure CN115896518B_ABST
Patent Text Reader

Abstract

The present invention provides a method for preparing an oriented carbon nanotube-graphene / copper composite material. The initial reinforcing phase is multi-walled carbon nanotubes and graphene nanosheets, and the carbon nanotubes and graphene are functionalized by mixed acid pretreatment to improve their dispersibility; the carbon nanotubes are nickel-plated to make them magnetic, and under the action of an external magnetic field, ultrasonic dispersion technology is combined with magnetic stirring to form a three-dimensional spatial network structure with graphene nanosheets that are not nickel-plated, thereby achieving orderly combination between the reinforcing phases; subsequently, intermittent vacuum ball milling is used to fully combine it with copper powder to obtain a composite powder, and an external magnetic field treatment is used again to make the composite powder oriented, and SPS vacuum sintering is combined to prepare an oriented carbon nanotube-graphene / copper composite material. In addition, the composite addition amount of the reinforcing phase carbon nanotube-graphene is only 0.1wt%~0.15wt%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials, and in particular relates to a method for preparing an oriented carbon nanotube-graphene / copper composite material. Background Art

[0002] Copper metal is widely used in key fields such as aerospace, rail transportation, electrical and electronic industries due to its excellent electrical and thermal conductivity and excellent processing performance. With the continuous development of industrial technology, the application requirements for copper metal are also developing in a diversified direction such as high strength, high electrical conductivity, and good wear resistance. Copper-based composite materials have good thermal and electrical conductivity, and their tensile strength, wear resistance and corrosion resistance are greatly improved compared to pure copper. They not only retain the excellent electrical conductivity of copper, but also overcome the disadvantage of insufficient hardness, so they have become a hot spot of current research.

[0003] Carbonaceous materials have the characteristics of low density and high strength, and are excellent reinforcements for metal-based composite materials. One-dimensional carbon nanotubes have the characteristics of high strength, high elastic modulus, high aspect ratio, excellent electrical and thermal conductivity, low axial expansion coefficient, good thermal stability and acid and alkali resistance; two-dimensional graphene has large surface area, light weight, excellent mechanical properties, unique electronic and thermal properties, so carbon nanotubes and graphene are considered to be ideal reinforcement materials in metal-based composite materials.

[0004] Both carbon nanotubes and graphene are nanocarbon materials, but due to their different structures, the performance they exhibit is also different. According to relevant research reports, the hybrid of one-dimensional carbon nanotubes and two-dimensional graphene will form a three-dimensional structure through spontaneous π-π bond interaction, thereby improving the dispersibility and strengthening effect. This multiphase synergistic reinforcement is an effective method to obtain composite materials with higher performance by combining the advantages of different reinforcement materials.

[0005] In the existing preparation process of copper-based composite materials, one-dimensional carbon nanotubes and two-dimensional graphene are often used as reinforcement phases. Chinese patent CN202010122893.2 discloses a method for preparing oriented CNTs / Cu composite materials by electromagnetic field-assisted electrophoretic deposition. Oriented CNTs / Cu is prepared by magnetic field-assisted electrophoretic deposition. The oriented reinforcement phase improves the mechanical properties in this direction to a certain extent, but the single reinforcement contributes only limitedly to the performance of the composite material and cannot significantly improve the mechanical properties of the material. Chinese patent No. 202110542727.2 discloses a method for preparing a carbon nanotube-graphene-graphene quantum dot synergistically enhanced copper-based composite material. Although the use of 0.3wt% composite reinforcement makes the prepared composite material close to the conductivity of the matrix copper, due to its inability to control the enhanced bonding mode, the tensile strength is only increased by 22.4%, and the performance enhancement effect is poor. Chinese patent CN112267040A adopts graphene oxide and carboxylation carbon nanotube as initial reinforcement phase. Although the composite material prepared by ball milling and sintering process can maintain excellent electrical conductivity, graphene oxide and carboxylation carbon nanotube are expensive, and it is also impossible to control the combination mode of graphene oxide and carboxylation carbon nanotube. When constructing three-dimensional network reinforcement phase, a certain degree of agglomeration will still occur, which has a great impact on the performance of composite materials. When most existing processes select carbon nanotubes and graphene as reinforcement phases, the combination mode of reinforcement phases presents a disordered state, and the tensile strength of composite materials is increased by about 1%~50% relative to the matrix, and the performance improvement range is not large, and some processes have certain losses compared to the matrix copper composite material conductivity after adding reinforcement phases. Based on this, the present invention prepares a reinforcement of three-dimensional network space structure by the synergistic effect between carbon nanotubes and graphene, and the combination form of the reinforcement phase is directional combination in combination with the external magnetic field regulation, so that the reinforcement phase is orderly combined, and the enhancement efficiency is maximized. The wet grinding process is used to achieve full combination of the matrix and the reinforcement phase under the premise of retaining the material structure to a large extent, and then the composite powder is oriented in the axial direction through an external magnetic field, and the oriented carbon nanotube-graphene / copper composite material is prepared in combination with SPS vacuum sintering. The preparation process of the present invention is simple, the reinforcement phase ratio is low, and the reinforcement phase is oriented and combined, the composite powder is oriented, and the mechanical property improvement rate of the prepared composite material is high, and a high electrical conductivity can be maintained. Summary of the invention

[0006] The main purpose of the present invention is to provide a preparation method of an oriented carbon nanotube-graphene / copper composite material, which can directional bond the reinforcing phase and directional arrange the composite powder by applying an external magnetic field, so that the three-dimensional network reinforcing phase structure is controllable, and the composite powder is directional arranged along the axial direction, thereby greatly improving the axial mechanical properties of the material and maintaining a high level of electrical conductivity, thereby providing a feasible method for improving the mechanical properties of copper-based composite materials.

[0007] In order to achieve the above-mentioned purpose, the present invention provides a method for preparing an oriented carbon nanotube-graphene / copper composite material, which uses mixed acid to pre-treat carbon nanotubes and graphene to purify and improve their dispersibility; nickel-plating the carbon nanotubes to make them magnetic; using ultrasonic technology and magnetic stirring and assisted by an external electromagnetic field to achieve dispersion and oriented combination of magnetized carbon nanotubes and graphene nanosheets; using vacuum ball milling to combine the copper matrix with the reinforcement phase, and then placing the composite powder in an electromagnetic field again for oriented treatment, so that the composite powder is oriented in the axial direction, and is formed by SPS vacuum sintering. The specific technical scheme is as follows:

[0008] (1) Concentrated nitric acid and concentrated sulfuric acid are mixed in a volume ratio of 1:3, an appropriate amount of carbon nanotubes or graphene is added, and ultrasonic treatment is performed for 60 minutes, followed by magnetic stirring for 7 hours, thereby improving the dispersibility of carbon nanotubes and graphene by introducing functional groups.

[0009] (2) activating and sensitizing the carbon nanotubes after acid treatment obtained in step (1), filtering, washing and drying; subsequently, performing chemical nickel plating on the surface, repeatedly washing, filtering, drying and setting aside.

[0010] (3) Weighing the graphene treated with acid in step (1) and the nickel-plated carbon nanotubes prepared in step (2) in proportion, placing them in ethanol, and ultrasonically dispersing them for 60 min. After forming a suspension, magnetic stirring is performed for 120 min to fully combine them to form a three-dimensional spatial structure, and then using an electromagnetic field to perform directional treatment.

[0011] (4) placing a certain mass of copper powder and the suspension prepared in step (3) in a vacuum ball mill for 240 minutes, with the ball-to-material mass ratio controlled at 10:1, so that the copper powder surface is fully loaded with oriented carbon nanotubes-graphene by ball milling, and then achieving solid-liquid separation by suction filtration, and obtaining a composite powder by vacuum drying.

[0012] (5) The graphite mold is placed in a magnetic field, and the composite powder prepared in step (4) is slowly added thereto. The mold is formed by SPS, sintered at 800°C, with a heating rate of 100°C / min, a holding time of 10min, a sintering pressure of 50MPa, and a vacuum degree of 0.1Pa~5Pa.

[0013] The preparation method of an oriented carbon nanotube-graphene / copper composite material described in the present invention has a composite addition amount of reinforcing phase carbon nanotube-graphene of only 0.1wt%~0.15wt%. Since the cost of carbon nanotubes and graphene is relatively high, the low addition amount can greatly reduce the preparation cost of the composite material. The present invention realizes the directional combination of magnetized carbon nanotubes and graphene nanosheets through an external magnetic field, thereby obtaining a carbon nanotube-graphene three-dimensional network structure with controllable orientation, strengthening the synergy between carbon nanotubes and graphene; and the composite powder prepared by vacuum ball milling is treated with a magnetic field again to make the composite powder oriented and arranged in the axial direction, and the obtained composite material is an oriented carbon nanotube-graphene / copper composite material, thereby greatly improving the axial mechanical properties of the composite material and maintaining a high level of electrical conductivity.

[0014] Based on the above technical solution, the preparation method and application of the present invention have the following beneficial effects:

[0015] (1) Graphene and carbon nanotubes are purified by mixed acid pretreatment, and oxygen-containing functional groups are introduced to improve their dispersibility in ethanol, thereby solving the problem of poor bonding with the matrix due to their own agglomeration.

[0016] (2) The pre-dispersion-wet grinding process is used to reduce the damage to the original material structure caused by ball milling during the preparation process, thereby protecting the original structural performance of the material to a greater extent.

[0017] (3) Through the assistance of electromagnetic fields, the directional bonding of one-dimensional magnetized carbon nanotubes and two-dimensional graphene nanosheets can be simply and effectively ensured, avoiding internal agglomeration during the reinforcing bonding process, thereby strengthening the synergistic effect between the reinforcing phases and forming a structurally controllable three-dimensional reinforcing phase.

[0018] (4) With the assistance of electromagnetic field, the three-dimensional reinforced carbon nanotube-graphene with magnetic properties can be combined with the matrix copper powder and then drive the composite powder to be oriented along the axial direction in a mold placed in a magnetic field, thereby preparing an oriented carbon nanotube-graphene / copper composite material, and the axial strength of the composite material is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of the directional arrangement process of the enhanced phase carbon nanotube-graphene in Example 1.

[0020] Figure 2 Schematic diagram of the preparation process of the aligned carbon nanotube-graphene / copper-based composite material in Example 1.

[0021] Figure 3 This is a schematic diagram of the construction of the electromagnetic field in Example 1. DETAILED DESCRIPTION

[0022] The present invention will be further described below in conjunction with specific embodiments.

[0023] Example 1 (0.05wt.%CNTs-0.05wt.%GNPs / 99.90wt.%Cu) Orientation

[0024] (1) Pretreatment of carbon nanotubes and graphene with mixed acid: 1 g of carbon nanotubes and 1 g of graphene were placed in 100 ml of mixed acid solution (25 ml of concentrated nitric acid + 75 ml of concentrated sulfuric acid) and ultrasonically treated for 60 min. After forming a suspension, magnetic stirring was performed for 7 h to mix evenly, and then vacuum dried for use.

[0025] (2) Nickel plating of carbon nanotubes: The acid-treated carbon nanotubes obtained in step (2) are placed in a SnCl 2 The mixture was ultrasonically treated for 30 min in a mixed solution of (0.1 mol / L) and HCl (10 ml / L), filtered, washed and dried; after drying, placed in PdCl 2 The carbon nanotubes were ultrasonically treated in a mixed solution of (0.25 g / L) and HCl (5 ml / L), filtered, washed and dried; 0.5 g of the treated carbon nanotubes were placed in NiSO 4 (0.1mol / L), NaH 2 PO 2 (0.15mol / L), Na 3 C 6 H 5 O 7 (0.15 mol / L) and NH 4 The mixed solution of Cl (0.2 mol / L) was ultrasonicated for 10 min, then plated in a constant temperature water bath at 85°C for 30 min, filtered, washed to neutrality and dried for later use.

[0026] (3) Preparation of oriented carbon nanotube-graphene mixed suspension: Weigh 0.025 g of graphene prepared in step (1) and 0.025 g of nickel-plated carbon nanotubes prepared in step (2) and add them to an ethanol solution at the same time, and ultrasonically disperse them for 60 minutes. After a stable suspension is formed, stir them magnetically for 120 minutes to make them uniform. Then, place the beaker containing the suspension in an electromagnetic field. When the switch is closed, the energized spiral coil generates a stable electromagnetic field due to the passage of direct current. The magnetic field is stable and the magnetic field strength is 1-2 T. Under the action of the magnetic field, the magnetized carbon nanotubes are oriented along the direction of the magnetic lines of force and are directionally combined with the graphene nanosheets.

[0027] (4) Preparation of oriented carbon nanotube-graphene / Cu composite powder: 49.95g of copper powder and the mixed suspension prepared in step (3) were placed in a ball mill, 500g of grinding balls were added and vacuum was evacuated. Subsequently, the mixture was ball milled for 240min using a planetary ball mill, the ball milling speed was 300r / min, the interval time was 10min, and the operation mode was alternating operation. After the ball milling was completed, the grinding balls in the ball mill were taken out, and the composite powder and ethanol were separated into solid and liquid by suction filtration, and then placed in a vacuum drying oven for drying for 24h.

[0028] (5) Molding of oriented carbon nanotube-graphene / copper composite powder: Place the graphite mold in an electromagnetic field, close the switch, and slowly add the composite powder into the mold so that the carbon nanotube-graphene / Cu composite powder is oriented along the direction of the magnetic field lines, and the direction of the magnetic field lines is parallel to the axial direction of the final material. SPS vacuum sintering solidification, the sintering temperature is controlled at 800℃, the heating rate is 100℃ / min, the sintering pressure is 50MPa, the vacuum degree is controlled at 0.1~5Pa, and the temperature is kept for 10min before cooling with the furnace.

[0029] Through experimental tests: the axial tensile strength of the oriented carbon nanotube-graphene / copper composite material is 368.42MPa and the electrical conductivity is 98.91IACS%.

[0030] Example 2 (0.05wt.%CNTs-0.05wt.%GNPs / 99.90wt.%Cu) non-oriented

[0031] (1) Pretreatment of carbon nanotubes and graphene with mixed acid: 1 g of carbon nanotubes and 1 g of graphene were placed in 100 ml of mixed acid solution (25 ml of concentrated nitric acid + 75 ml of concentrated sulfuric acid) and ultrasonically treated for 60 min. After forming a suspension, magnetic stirring was performed for 7 h to mix evenly, and then vacuum dried for use.

[0032] (2) Preparation of carbon nanotube-graphene mixed suspension: Weigh 0.025 g of the carbon nanotubes and graphene prepared in step (1) and add them to an ethanol solution at the same time, and disperse them ultrasonically for 60 min. After a stable suspension is formed, stir the mixture magnetically for 120 min to mix them evenly.

[0033] (3) Preparation of carbon nanotube-graphene composite powder: 49.95 g of copper powder and the mixed suspension prepared in step (2) were placed in a ball mill, 500 g of grinding balls were added and vacuum was evacuated. Subsequently, the mixture was ball milled for 240 min using a planetary ball mill, the ball milling speed was 300 r / min, the interval time was 10 min, and the operation mode was alternating operation. After the ball milling was completed, the grinding balls in the ball mill were taken out, the composite powder and ethanol were separated into solid and liquid by suction filtration, and the mixture was placed in a vacuum drying oven for drying for 24 h.

[0034] (4) Forming of carbon nanotube-graphene composite powder: The composite powder is placed in a graphite mold and solidified by SPS vacuum sintering. The sintering temperature is controlled at 800°C, the heating rate is 100°C / min, the sintering pressure is 50MPa, the vacuum degree is controlled at 0.1~5Pa, and the mixture is kept warm for 10min before cooling in the furnace.

[0035] Through experimental tests: the axial tensile strength of the composite material is 327.16 MPa and the electrical conductivity is 93.94 IACS%.

[0036] Comparative Example 1 (100wt%Cu)

[0037] (1) Preparation of pure copper powder: 50g of copper powder and 100ml of ethanol solution are placed in a ball mill, 500g of grinding balls are added and vacuum is applied. Ball milling is performed for 240min using a planetary ball mill, the ball milling speed is 300r / min, the interval time is 10min, and the operation mode is alternating operation. After the ball milling is completed, the grinding balls in the ball mill are removed, the pure copper powder and ethanol are separated by solid-liquid filtration, and then placed in a vacuum drying oven for drying for 24h.

[0038] (2) Forming of pure copper samples: Pure copper powder was placed in a graphite mold and solidified by SPS vacuum sintering. The sintering temperature was controlled at 800 °C, the heating rate was 100 °C / min, the sintering pressure was 50 MPa, the vacuum degree was controlled at 0.1~5 Pa, and the sample was kept warm for 10 min before being cooled in the furnace.

[0039] Through experimental tests: the axial tensile strength of the pure copper sample is 184.90MPa and the electrical conductivity is 92.28IACS%.

[0040] The tensile strength and electrical conductivity of the materials prepared in Examples 1-2 and Comparative Example 1 were tested, and after comparative calculation with Comparative Example 1, the test results are listed in Table 1.

[0041] Table 1

[0042]

[0043] From the test results in Table 1, it can be seen that under the synergistic effect of the reinforcing phase graphene-carbon nanotubes, the tensile strength of the composite material is significantly improved compared with pure copper. The axial tensile strength of the oriented carbon nanotube-graphene / copper composite material prepared by electromagnetic field assistance is 368.46MPa, which is 183.52MPa higher than the axial tensile strength of pure copper and 41.26MPa higher than the composite material prepared without directional treatment. In addition, the conductivity of the oriented carbon nanotube-graphene / copper composite material is 98.91IACS%, which is higher than pure copper and the composite material prepared without directional treatment. It can be seen that the directional treatment of one-dimensional carbon nanotubes and two-dimensional graphene is directional and combined, and the reinforcement efficiency of the reinforcing phase is improved.

[0044] Figure 1-3 They are the directional arrangement process of enhanced carbon nanotube-graphene, the preparation process of directional carbon nanotube-graphene / copper composite materials and the schematic diagram of the construction of the electromagnetic field. When constructing the three-dimensional network structure of carbon nanotube-graphene, under the action of the magnetic field, the carbon nanotubes are directional arranged on the graphene nanosheets; in the graphite mold, the magnetic carbon nanotubes also drive the directional distribution of the carbon nanotube-graphene / copper composite powder through the action of the electromagnetic field. In addition, it can be seen from the figure that the preparation process and the magnetic field are simple to build, easy to operate, and have low equipment requirements and are easy to implement.

[0045] The method of the present invention has been described through preferred implementation examples. In the specific embodiments described above, it should be particularly pointed out that the above is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing an aligned carbon nanotube-graphene / copper composite material, characterized in that: The following steps are involved: 1) Functional pretreatment of carbon nanotubes and graphene: Place carbon nanotubes and graphene in mixed acid for ultrasonic treatment to connect hydrophilic groups; 2) Nickel plating of carbon nanotubes: Activate and sensitize the carbon nanotubes treated with acid obtained in step 1), filter, wash and dry; then perform chemical nickel plating on the surface, wash and filter repeatedly, dry and set aside; 3) 3D construction of aligned carbon nanotube-graphene: low-content nickel-plated carbon nanotubes and the acid-treated graphene obtained in step 1) are weighed and placed in an ethanol solution, and a carbon nanotube-graphene suspension is obtained by ultrasonic dispersion and magnetic stirring, and the magnetized carbon nanotubes are oriented and combined with the graphene nanosheets by magnetic field treatment to enhance the synergistic effect between the carbon nanotubes and the graphene; 4) Preparation of composite powder: The oriented carbon nanotube-graphene mixed solution obtained in step 3) and copper powder are placed in a vacuum ball mill, and the copper powder is increased in contact area by a planetary ball mill so as to combine with the reinforcing phase carbon nanotube-graphene. Subsequently, the composite powder and the ethanol solution are separated by suction filtration and placed in a vacuum drying oven for drying; 5) Consolidation of the composite material: placing the graphite mold in an electromagnetic field, and slowly adding the dried composite powder obtained in step 4) to orient the composite powder in the mold, and then solidifying the powder by an SPS vacuum sintering apparatus to obtain an oriented carbon nanotube-graphene / copper composite material; In the step 3), the ultrasonic treatment time is 60 minutes, the magnetic stirring time is 120 minutes, and the external magnetic field auxiliary process is that when the switch is closed, the energized spiral coil generates a stable magnetic field in the container due to the passage of direct current, and the magnetic field strength is 1-2T. Under the action of the magnetic field, the magnetized carbon nanotubes are distributed in the solution in a direction and are directionally combined with the graphene nanosheets; In the step 4), the ball milling is wet milling, the ball milling time is 240 min, the rotation speed is 300 r / min, the ball-to-material mass ratio is 10:1, and the ball milling method is intermittent 10 min, alternating operation; In the step 5), the strength of the external magnetic field is 1-2 T, and the magnetic field assisted process is that when the switch is closed, the energized spiral coil generates a stable magnetic field in the graphite mold due to the passage of direct current, and the composite powder is slowly added, so that the composite powder is arranged in a direction in the mold; In the step 5), the subsequent SPS vacuum sintering temperature is controlled at 800°C, the heating rate is 100°C / min, the holding time is 10min, the sintering pressure is controlled at 50MPa, and the vacuum degree is maintained at 0.1~5Pa; In the oriented carbon nanotube-graphene / copper composite material, the composite addition amount of the reinforcing phase carbon nanotube-graphene is 0.1wt%-0.15wt%.

2. The method for preparing an aligned carbon nanotube-graphene / copper composite material according to claim 1, characterized in that: In the step 1), the carbon nanotubes are multi-walled carbon nanotubes with an outer diameter of 20-30 nm and a length of 0.5-2 μm, and the graphene is graphene nanosheets with a thickness of 4-20 nm and a size of 5-10 μm.

3. The method for preparing an aligned carbon nanotube-graphene / copper composite material according to claim 1, characterized in that: In the step 1), the acid treatment uses concentrated nitric acid and concentrated sulfuric acid, and the volume ratio of the two is 1:

3.

4. The method for preparing an aligned carbon nanotube-graphene / copper composite material according to claim 1, characterized in that: In step 2), a mixed solution of 0.1 mol / L SnCl2 and 10 mol / L HCl is used for sensitization treatment, a mixed solution of 0.25 g / L PdCl2 and 5 mol / L HCl is used for activation treatment, and a mixed solution of 0.1 mol / L NiSO4, 0.15 mol / LNaH2PO2, 0.15 mol / L Na3C6H5O7 and 0.2 mol / L NH4Cl is used for nickel plating.

Citation Information

Patent Citations

  • Method for preparing oriented CNTs / Cu composite materials through electromagnetic field auxiliary electrophoretic deposition method

    CN111118583A

  • Preparation method of graphene-carbon nanotube / copper-based composite material

    CN112267040A

  • A method for preparing multidimensional carbon material composite reinforced copper-based materials

    CN113278838B

  • Preparation method of carbon nanotube reinforced copper-based composite material

    CN110560698A

  • Preparing method for carbon nanotube reinforced copper-based composite material

    CN110983211A